Family factors as predictors of violent behaviour among in-school adolescents in Ibadan North Local Government Area of Oyo State, Nigeria (2015)
The study examined family factors as predictors of violent behaviour of in school adolescents in Ibadan North Local Government Area of Oyo State, Nigeria. Descriptive survey research design was employed in the study. A sample of 277 respondents was selected using stratified random sampling. Three research hypotheses were tested. Self-developed and validated questionnaire with reliability co-efficient of 0.71 was used to collect data. Data were analysed with the use of inferential statistics of regression at 0.05 level of significance. The results showed that joint effect of family factors (career family, family financial difficulty and violent family) on inschool adolescents’ violent behaviour was significant (F(3,273)=119.181 ; R=0.753; R2=0.567; R. Adj = 0.562; P<.05). Thus, it was concluded that violent behaviour is a major cause of injuries and death among adolescents. Among others, it was recommended that poverty alleviation programme, responsible parenthood as well as family life education should be provided by government.